(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The article examines the phenomenon whereby an increase in the ability of commercial banks to extend credit to various economic sectors and the general population is accompanied by a rise in the proportion of non-performing loans. It analyzes the causes of non-performing loans, their impact on banking operations, and provides conclusions and recommendations for reducing their share.